Comparison of the socioeconomic development roles played by different forestry companies in rural communities of Mkhondo local municipality in Mpumalanga Province, South Africa - Tshidzumba, Ratsodo Phillip (University of Pretoria, 2023)
Dissertation (MSc (Forest Management and the Environment))--University of Pretoria, 2023.